Poly (γ) glutamic acid: a unique microbial biopolymer with diverse commercial applicability - Elbanna, Khaled; Alsulami, Fatimah S.; Neyaz, Leena A.; Abulreesh, Hussein H. (Frontiers in Microbiology, 2024)
Microbial biopolymers have emerged as promising solutions for environmental pollution-related human health issues. Poly-γ-glutamic acid (γ-PGA), a natural anionic polymeric compound, is composed of highly viscous homo-polyamide of D and L-Glutamic acid units. The extracellular water solubility of PGA biopolymer facilitates its complete biodegradation and makes it safe for humans. The unique properties have enabled its applications in healthcare, pharmaceuticals, water treatment, foods, and other domains. It is applied as a thickener, taste-masking agent, stabilizer, texture modifier, moisturizer, bitternessreducing agent, probiotics cryoprotectant, and protein crystallization agent in food industries. γ-PGA is employed as a biological adhesive, drug carrier, and non-viral vector for safe gene delivery in tissue engineering, pharmaceuticals, and medicine. It is also used as a moisturizer to improve the quality of hair care and skincare cosmetic products. In agriculture, it serves as an ideal stabilizer, environment-friendly fertilizer synergist, plant-growth promoter, metal biosorbent in soil washing, and animal feed additive to reduce body fat and enhance egg-shell strength.